CORRELATION OF LACTOFERRIN LEVELS IN BREAST MILK WITH MATERNAL HAEMOGLOBIN PERCENTAGE AMONG LACTATING WOMEN OF LOW AND HIGH SOCIOECONOMIC STATUS - Taqi, Tabinda; Qazi, Abroo Fatima; Qazi, Sumayya; Shaikh, Din Muhammad; Kazi, Navaid (Pakistan Journal of Physiology, 2017)
Background: Due to considerable lack of knowledge among working class women and housewives (with no/low literacy level) about the prime sources of dietary iron and the use for their own health during child bearing age is a dilemma that affects the entire family system resulting in decreased haemoglobin level and consequent anaemia during and after pregnancy and its effect on quality of breast milk due to which the child suffers. Objective: To assess the lactoferrin levels in breast milk with haemoglobin percentage among lactating women of low and high socio-economic status and to compare both the groups for the same. Methodology: A total of 60 lactating mothers were involved in this study. Among them 30 belonged to the population of high socioeconomic status (H group) and 30 belongs to the population of low socioeconomic status (L group). The demographic data was compiled on a questionnaire proforma. 2 ml of blood was collected in EDTA bottles in each case and sent to clinical laboratory for the estimation of haemoglobin%. 5–10 ml of breast milk was collected with breast pump into sterile bottle. The assistance of nurses on duty was employed to aseptically collect the samples. The mother’s consent was also obtained before collection. The samples were transported on dry ice to the clinical laboratory for estimation of the lactoferrin levels using ELISA Method. Results: The mean haemoglobin saturation in whole blood was calculated, in L group was 52.9% as compared to 63.6% in H group. These findings were found statistically significant (p<0.05) in each group and also when comparing both groups. The mean lactoferrin level in L group was 2.472 mg/ml as compared to 3.56 mg/ml in H group. These findings were found statistically significant (p<0.05) in each group and also when comparing both groups. The results of lactoferrin level were also found significant in all age groups. Conclusion: The current study highlights the importance of health of lactating women in order to improve the quality of milk for their babies. The data extracted shows significant difference in the lactoferrin levels of milk between low and high socioeconomic population which significantly correlates with percentage of haemoglobin, and also in different age groups of both classes indicated by the level of the lactoferrin in their milk. Pak J Physiol 2017;13(4):30–3